Ácido salicílico na qualidade pós-colheita de frutos, hortaliças folhosas e flores - Borsatti, Fabiana Chiamulera (2014)
The aim of this work was to evaluate the salicylic acid (SA) effect applied in the blackberry, acerola, kale, spinach and roses postharvest for the conservation and resistance induction. The experimental design was completely randomized, with four replications and the treatments were based on the solutions concentrations with SA 0.0, 0.5, 1.0, 1.5 and 2.0 mM. The vegetable organs from the cultures were immersed in the solutions with different treatments and after it was stored at 8 °C. For the fruit (blackberry and acerola) the fresh matter weight losses, total soluble solids (TSS), titratable acidity (TA), ascorbic acid and rot incidence were evaluated. During the intervals of 24, 48, 96 and 192 hours after treatment application, fruit samples were separated for total protein, anthocyanins, flavonoids and phenylalanine ammonia lyase (PAL), chitinase and β-1,3-glucanase enzymes activities were determinate. These analyzes were applied for all treatments, with the exception of chitinase and β-1,3-glucanase, which were evaluated only for fruits treated with 2.0 mM concentration and control treatment. For the vegetables (kale and spinach) the fresh mass losses, rot incidence, vitamin C and chlorophyll were evaluated. During the intervals of 24, 48, 96 and 192 hours after treatment application, the total protein, total phenols, phenylalanine ammonia lyase (PAL) and peroxidase enzimes were evaluated. For roses the peduncle curvature, turgescence and petals darkening were visual evaluated. When the experiment time finished, the fresh weight losses and the leaf chlorophyll content were evaluated. During 24 hour intervals, collected a petals sample to determine the total protein and PAL and peroxidase activities. For blackberries there was an increase of protein level and the β-1,3-glucanase activation with the application of SA. The anthocyanins and flavonoids contents and the PAL activity, had changes during the experiment due to the SA application. The treatments were not significant for fresh mass losses, TA, TSS, rot incidence, ascorbic acid and chitinase activities for this fruit. In the acerola, the TA was higher and TSS were lower in the fruit treated with SA. The treatments were not significant for fresh mass losses, of ascorbic acid content. There was a reduction in the fruit rots incidence with application of SA and an activation of chitinase, β-1,3-glucanase and PAL activity enzymes, and it increased anthocyanins and flavonoids contents for acerola. The SA application in the kale kept the protein and total phenol with higher levels and it interfere in the peroxidases activity. There was no significant treatment effect for fresh weight losses, vitamin C, chlorophyll, rot incidence and PAL activity. The highest SA concentrations decreased the fresh weight losses and they kept the higher proteins contents for spinach. The treatments did not affect the chlorophyll content, total phenolics and peroxidase and PAL activities.There wasn't treatment effect about total protein content, PAL and peroxidase activity in the roses stems. The rose treated with the highest SA concentration presented higher grade evaluation for peduncle curvature, turgescence and petals darkening, ie, the best visual aspect.